Bovine spongiform encephalopathy (BSE) cases born after the total feed ban. (13th July 2017) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Fernández Escámez, Pablo Salvador; Gironés, Rosina; Herman, Lieve; Koutsoumanis, Kostas; Lindqvist, Roland; Nørrung, Birgit; et al.
Abstract: Sixty bovine spongiform encephalopathy (BSE) cases of Classical or unknown type (BARB‐60 cases) were born after the date of entry into force of the EU total feed ban on 1 January 2001. The European Commission has requested EFSA to provide a scientific opinion on the most likely origin(s) of these BARB‐60 cases; whether feeding with material contaminated with the BSE agent can be excluded as the origin of any of these cases and, if so, whether there is enough scientific evidence to conclude that such cases had a spontaneous origin. The source of infection cannot be ascertained at the individual level for any BSE case, including these BARB‐60 cases, so uncertainty remains high about the origin of disease in each of these animals, but when compared with other biologically plausible sources of infection (maternal, environmental, genetic, iatrogenic), feed‐borne exposure is the most likely. This exposure was apparently excluded for only one of these BARB‐60 cases. However, there is considerable uncertainty associated with the data collected through the field investigation of these cases, due to a time span of several years between the potential exposure of the animal and the confirmation of disease, recall difficulty, and the general paucity of documented objective evidence available in the farms at the time of the investigation. Thus, feeding with material contaminated with the BSE agent cannot be excluded as the origin of any of the BARB‐60 cases, nor is it possible to definitively attribute feed as the cause of any of the BARB‐60 cases. A case of disease is classified as spontaneous by a process of elimination, excluding all other definable possibilities; with regard to the BARB‐60 cases, it is not possible to conclude that any of them had a spontaneous origin.